ANALISIS PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH SEBAGAI UPAYA PENINGKATAN KEAKTIFAN PROSES PEMBELAJARAN DI PONDOK PESANTREN ISLAMIC CENTRE ALHIDAYAH KAMPAR - Munjiatun Munjiatun; Isjoni Isjoni; Marzuki Marzuki (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2021)
The basic concept of school-based management is the transfer of authority or responsibility in school management from the central government to the school level. The background of this research is to find out the authority and responsibility of the government, schools and madrasah committees in school management. The purpose of this study was to: (1) analyze the implementation of SBM; (2) describe the increased activity of the SBM learning process; (3) describe obstacles to implementing SBM, and (4) describe the efforts made to overcome obstacles in implementing SBM. This study uses a descriptive method with a qualitative approach. The data used in this study is how to implement SBM and want to cover the improvement of the activeness of processes, obstacles, and efforts made to implement SBM. Islamic Boarding School in Kampar, Riau Province. The results of this study appear in all students. This learning process is delivered by the teacher. Then the obstacle faced by the foundation for implementing school-based management at the Islamic Center of Al-Hidayah Kampar Islamic Boarding School is the low commitment of teachers. Next, the teacher tries to package learning using various approaches, methods, and media. Variations in the method of discussion and question and answer, choosing words that are suitable for students, which is a means of enhancing students' activeness, in addition to teachers also trying to motivate students by giving stars activeness when there are students who can answer the quiz given by the teacher.